STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SMP NEGERI 50 BENGKULU UTARA - Gunawan Siregar, Indra; Somantri , Manap; Connie (UNIVERSITAS BENGKULU, 2024)
This study aims to describe the strategies of school principals in improving the professional competence of teachers in North Bengkulu 50 Public Junior High School. Research using descriptive qualitative method. The research subjects were school principals and teachers at North Bengkulu 50 Public Junior High School. Research data obtained from observations, interviews and documentation. Research data analysis includes data reduction , data presentation, verification and drawing conclusions. The results showed that the principal's strategy in increasing the professional competence of teachers in North Bengkulu 50 Public Junior High School was especially good, but the principal needed to find a better and more appropriate strategy for increasing professional competence in the aspect of lesson planning, especially in increasing mastery of learning material, structure , scientific concepts and mindsets that support the subjects being taught.